"Jobbos" and the "wageless life": Exploring work and responsibility in the anti‐fracking movement in Lancashire, United Kingdom. Issue 1 (10th December 2022) - O'Brien, Sarah G.P.
ABSTRACT: Drawing on ethnographic research at an anti‐fracking encampment at Preston New Road (PNR) in Lancashire, England, this article explores activists' perceptions of work and responsibility. I examine their protest activities and explore how work is understood, disrupted, and contested; what this means for my interlocutors' engagement with monetary compensation; and how this is reinforced by the extractive nature of the activity they are contesting. I show how through protesting, monitoring, and maintaining a presence on site, interlocutors worked to ethically and materially disentangle themselves from the reality fueled by hydrocarbon extraction. While paid work was deemed ethically problematic in this context, at stake for my interlocutors was the web of relationships in which financial and practical support was received and shared. By drawing on research on activism and dynamics of prefiguration, I show how the work of activism at PNR was predicated on balancing agency with responsibility in a complex and powerful web of responsible relationships. Reconciling agency and responsibility was integral to the ethical orientations on which the anti‐fracking community was built and the realities it aspired to create.